Perulernaea gamitanae (Crustacea: Lerneaidae) in juvenile Colossoma macropomum (Characiformes: Serrasalmidae) in semi-intensive fish farming in Loreto, Peru - Arbildo Ortiz, Humberto (2019)
The aim of this study was to determine the presence of the copepod Perulernaea gamitanae in juveniles of Colossoma macropomum and to relate the abundance of the parasite with the length and weight of the hosts. Thirty specimens of 29.1 ± 2.8 cm of total length and 506.3 ± 124.6 g of body weight from a semi-intensive fish farm in Maynas, Loreto (Peru) were evaluated. It was collected 120 individuals of P. gamitanae located in the buccal cavity and in the cartilages of the gills. The prevalence was 90%, the mean intensity was 4.4 parasites/infested fish, the average abundance was 4 parasites/fish, with an intensity range of 1 to 10 parasites/fish. The abundance of this copepod was related to the length and weight of the host. This is the second record of P. gamitanae in C. macropomun in fish farms in the Peruvian Amazon.